2018
DOI: 10.3171/2018.5.focus18166
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral amygdala stimulation reduces avoidance behavior in a predator scent posttraumatic stress disorder model

Abstract: OBJECTIVEThe predator scent model of posttraumatic stress disorder (PTSD) produces prolonged abnormal anxiety and avoidance-like behaviors. Increased basolateral amygdala activity has been shown to correlate with severity of PTSD symptoms in human studies. Modulation of this increased amygdala activity by deep brain stimulation led to improved symptoms in prior studies that used a foot shock model of inducing PTSD. The predator scent model is a different technique tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…In these studies, reciprocal inhibition is shown to occur between the amygdala "fear-on" neurons and vmPFC "fear-off" neurons via GABAergic inhibitory interneurons (Fig. 1c) [44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Proposal Of the Reciprocal Inhibition Modelmentioning
confidence: 93%
“…In these studies, reciprocal inhibition is shown to occur between the amygdala "fear-on" neurons and vmPFC "fear-off" neurons via GABAergic inhibitory interneurons (Fig. 1c) [44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Proposal Of the Reciprocal Inhibition Modelmentioning
confidence: 93%
“…For example, excitatory neurotransmission within BLA is required for anxiety-like symptoms and concurrent neural activation in rats after exposure to a live cat (Adamec et al, 2005; Blundell and Adamec, 2007). Similarly, high-frequency BLA stimulation reduces anxiety-like behavior in rats after exposure to cat urine (Dengler et al, 2018); an effect similar to informational lesion observed in deep-brain stimulation paradigms. Relationship between predator exposure, BLA and psychiatric conditions remains currently understudied; and represents an important opportunity to understand clinically abnormal fear in the future.…”
Section: Resultsmentioning
confidence: 80%
“…The amygdala-vmPFC network is characterized by a pattern of predominant bottom-up and top-down connectivity in the non-dissociative and dissociative subtypes, respectively (36). Additionally, amygdala activity is positively correlated with attentional bias toward threat (37-39) and re-experiencing symptoms (11,40,41) while vmPFC activity is positively correlated with attentional bias away from threat (14,42) and avoidance/dissociative symptoms (36,43,44). Findings from rodent studies indicate precise microcircuits that could at least in part underlie the reciprocal inhibition proposed by our model.…”
Section: Reciprocal Inhibition Model: Proposal For Attention Oscillatmentioning
confidence: 99%